SEGMENTATION OF CONSUMER GOODS COMPANY SUB SECTOR FOOD AND BAVERAGE BASED ON FINANCIAL RATIO USING K-MEANS CLUSTERING IN THE COVID-19 PERIOD 2019-2020 - Muhammad Randy Hidayatullah; Jerry Heikal (Sean Institute, 2023)
The impact that food and beverage companies will get from the COVID-19 pandemic can vary. The author feels that segmentation is needed to see the impact generated by the presence of the covid-19 pandemic on the overall number of companies in the food and beverage sub-sector by conducting a study. The data source for this research is the financial reports of all consumer goods companies in the food and beverage sub-sector on the Indonesia Stock Exchange for the period 2019 – 2020. This study uses an unsupervised learning method, assisted by K-Means clustering and based on a comparison of four operational variables from the financial ratio derived in the form of current ratio, inventory turnover, debt to equity, and return on equity. As a result, it was found that there had been a change in segmentation in several consumer goods companies in the food and beverage sub-sector during the COVID-19 period for the 2019-2020 period.